1993
DOI: 10.1055/s-2008-1063499
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Long-Term Results of the Nissen Fundoplication

Abstract: The Nissen fundoplication is the operative therapy of choice in children with symptomatic gastroesophageal reflux. In recent years several reports on specific complications of the Nissen fundoplication have been published. This report summarizes the complications in 45 patients on whom a Nissen fundoplication was performed in our clinic between 1979 and 1989. 18 patients (40%) showed early or late complications. In 10 patients (22%) reoperation was necessary. However, at follow-up with a mean period of 4 1/2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…At follow-up with a mean period of 8.7 years following Nissen fundoplication, 87.5 % showed good results without any residual symptoms. These clinical results compare favorably with previously published data from various centers (13,18,29,32). However, the complication rate was as high as 50 %.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At follow-up with a mean period of 8.7 years following Nissen fundoplication, 87.5 % showed good results without any residual symptoms. These clinical results compare favorably with previously published data from various centers (13,18,29,32). However, the complication rate was as high as 50 %.…”
Section: Discussionsupporting
confidence: 89%
“…Nissen fundoplication is the most widely used procedure and has been reported to give good control of gastroesophageal reflux. Several reports, however, documented a significantly high complication rate following the Nissen fundoplication (9, 13,29). For this reason, over the last 20 years, several reports have been published advocating other antireflux procedures (4-6, 8).…”
Section: Mots-elesmentioning
confidence: 99%
“…Delayed gastric emptying is a known predisposing factor for wrap failure [20,21]. Failed fundoplication can be a challenging problem and it is better avoided.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Although the initial treatment for Ger, especially in newborns is clinical 21 , surgical treatment may be indicated in cases where anatomical disorders are present or when clinical treatment is ineffective and associated with lifethreatening conditions 22,23 . In these instances, it has been demonstrated that the Nissen fundoplication can be accomplished safely with a low incidence of complications 24 .…”
Section: Discussionmentioning
confidence: 99%